A new species of Apostlethrips (Thysanoptera, Phlaeothripidae); an Australian genus from grass tussocks - Wang, Jun; Mound, Laurence; Tree, Desley J. (Zootaxa, 2019)
In most of the warmer parts of the world, a considerable diversity of thrips live only at ground level where they feed on fungi. In Australia, many such Phlaeothripidae species live in leaf-litter (Mound et al. 2013; Wang et al. 2019), but a different and smaller suite of thrips lives particularly at the base of tussocks of grasses and similar plants (Mound & Minaei 2006; Eow et al. 2014; Mound & Tree 2018). One genus in this suite, Apostlethrips, has been known only from two species (ThripsWiki 2019), both of which were taken from the base of Triodia grasses in the northern parts of Western Australia. The purpose of the present contribution is to describe a third species in this genus, taken from grasses near Darwin. This new species shares with the other two members of the genus the unusual character of a pair of rather stout and capitate ocellar setae (Fig. 1), but it differs in several other character states. As a result, a revised generic diagnosis is provided here. Pronotal setal abbreviations are as follows: am—anteromarginals; aa—anteroangulars; ml—midlaterals; epim—epimerals; pa—posteroangulars.